Трансформация оленеводства малочисленных народов Севера в XX – начале XXI в. (на примере эвенов и коряков Магаданской области) - Maltseva, N. V.; Мальцева, Н. В. (Издательство Тюменского государственного университета, 2016)
We consider the transformation of deer farms of the Evens and the Koryaks of the Magadan region for over a century. The basic historical periods (traditional, Soviet, post-Soviet) are characterized by qualitative changes in the economic activities and culture of indigenous small-numbered population. The traditional period of domestic reindeer breeding by people was little affected by the state. The Evens continued using complex economy (hunting, fishing, herding) – Tungus type of reindeer husbandry. Koryak reindeer husbandry had largeherd reindeer husbandry characteristic of Paleoasian type. In the Soviets there were a strong qualitative changes in all spheres of reindeer herders’ life. The Soviet model of modernization was a standardization of forms and methods of farming, lifestyle, culture, and the blurring of lines, that is a variety of public relations. In the post-Soviet period, reindeer husbandry remained only in two districts of the region – the North-Evenk and Srednekansk – where there was, in the first case, in the form of an organized municipal enterprise and, secondly, the tribal communities. Today reindeer herding in the Magadan region is almost gone. There is a small herd of grazing Even in the North of Even District. When the last reindeer herder will leave tundra, you can talk with certainty about the disappearance of reindeer husbandry and culture in the Magadan region. Рассмотрена история развития оленеводства малочисленных народов севера Магаданской области.